Optimizing antifungal dosing for invasive Cryptococcus infections: minimum inhibitory concentration distributions and pharmacokinetic/pharmacodynamic insights from 2010–2023 Antimicrobial Testing Leadership and Surveillance data - Liu, Chia-Ying; Lai, Chih-Cheng; Hsueh, Chun-Chung; Weng, Chih-Jen; Chang, Wei-Lun; Hsueh, Po-Ren; Jean, Shio-Shin (Frontiers in Pharmacology, 2025)
ObjectiveThe 2024 global cryptococcosis treatment guidelines suggests that fluconazole (FLC) combined with liposomal amphotericin B (AMB) and 5-flucytosine (5-FC) as the mainstay of treatment for systemic cryptococcosis. Although this 2024 guidelines also list recommend voriconazole (VRC), posaconazole (POS), and isavuconazole (ISA) as alternatives to FLC during the consolidation and maintenance phases, current data on distributions of minimum inhibitory concentrations (MICs) of global Cryptococcus isolates for antifungals—and studies evaluating the application of their pharmacokinetic (PK) profiles and pharmacodynamic (PD) indices in the treatment of systemic cryptococcosis—remain limited. To optimize antifungal dosing, integration of global MIC distributions for Cryptococcus isolates with PK/PD parameters for key antifungal agents is needed.MethodsThis study analyzed the MIC distributions from the 2010–2023 antifungal Antimicrobial Testing Leadership and Surveillance database, and determined epidemiological cutoff values for major Cryptococcus species.ResultsThe majority of invasive Cryptococcus isolates were classified as wild-type strains (>90%). We analyzed PK profiles (particularly central nervous system [CNS] penetration from the bloodstream), PD indices of antifungals (azoles and AMB) against yeasts. Based on 25 studies clearly describing PK–PD relationships, FLC and VRC were considered optimal choices because of superior CNS penetration. The optimal dose of FLC is 800–1,200 mg/day, whereas dosages of VRC and ISA do not require adjustment. Nevertheless, therapeutic drug monitoring for VRC is warranted during its prescription due to significant variability in plasma concentrations influenced by multiple factors. POS is not suitable for induction therapy in systemic cryptococcosis. Additionally, ISA is preferred over POS for consolidation therapy for Cryptococcus meningitis/meningoencephalitis (MME) based on differences in their PK profiles. Furthermore, a single 10 mg/kg dose of liposomal AMB—a cost-effective strategy—should be combined with 1,200 mg/day FLC and 5-FC, or alternatively VRC, as an effective induction-phase regimen for treating Cryptococcus MME.ConclusionDiverging from the 2024 guidelines, this study provides novel insights into the treatment of Cryptococcus MME based on MIC distributions and PK-PD indices for antifungal agents.